Penerapan Metode Pembelajaran Two Stay Two Stray untuk Meningkatkan Hasil Belajar Menghias Busana dengan Teknik Sulaman Fantasi pada Siswa Kelas XI-A Tata Busana di SMK Negeri 3 Metro Tahun Pelajaran 2018/2019 - Meri Mannaria Karokaro (eductum: Jurnal Literasi Pendidikan, 2022)
This study aims to improve learning outcomes by applying the Two Stay Two Stray (TSTS) type cooperative learning method in the subject of decorating clothes for students of class XI-A Fashion Design at SMK Negeri 3 Metro. This research is a classroom action research model of Kemmis and Taggart which was conducted in two cycles. Each cycle consists of three stages, namely: planning, implementation and observation, and reflection. The selected Basic Competence is to analyze fantasy embroidery designs in a product. The subjects of this study were students of class XI-A, totaling 38 students. The data collection method used in this study was the observation of the implementation of the TSTS learning method, performance tests, and documentation. While the data analysis used is descriptive data analysis in percentage. The Action Hypothesis is that there is an increase in learning outcomes in the Class XI-A Fashion Decorating subject trying to apply the TSTS learning method. The application of the Two Stay Two Stray (TSTS) learning method according to the syntax that is juxtaposed with the scientific approach aims to improve the learning outcomes of fashion decoration in class XI-A. The results showed that there was an increase in the value of learning to decorate clothes from the first cycle with an average of 75.98 to 84.67 in the second cycle, and the percentage of mastery learning increased from the first cycle of 57.14% to 100% in the second cycle.